The Eruptive Duality of a Filament on 2023 April 21 - Yue Fang; Jun Zhang (The Astrophysical Journal)
Here we study a filament eruption on 2023 April 21. The filament was composed of two segments, named S1 and S2. Initially, the brightening and bidirectionally plasmoid flows appeared inside S1, and then the west part of S1 (WS1) experienced rapid rising and eruption, accompanied by coronal dimming, flare ribbons, and a secondary flare ribbon. However, the east part of S1 (ES1) rose slowly and was confined. The material within ES1 drained back to its eastern footpoint, resulting in the footpoint brightening. In the later phase, the south footpoint of the stable extreme-ultraviolet (EUV) loops overlying ES1 was brightened also, which may result from the disturbance of drainage. During S1 eruption and activation, S2 remained stable. Nonlinear force-free field extrapolation shows that the footpoints of the magnetic field lines overlying WS1 are rooted on the flare ribbons, while the field lines overlying ES1, which share a negative field with other lines, correspond to the stable EUV loops. Based on potential field extrapolation, we calculate the decay index of the background fields overlying the filament. It indicates that the critical height of the torus instability of the fields overlying WS1 is lower than that overlying ES1. To interpret this filament eruption, we first put forward the eruptive duality, characterized by the eruption of the partial filament structure and the confinement of the other structure, and this duality is determined by the properties of the overlying fields.